Proyecto de evaluación de procesamiento y comercialización de colas de camarón orgánico al ajillo para la provincia de Santa Elena - Tapia Yagual, Liliana (2010)
In the presently project it is realized to study of market and financial feasibility for the implementation of to microempresa processor and to market of tail of organic shrimp to garlic, which will have to technology based on the treatment of preservation application in its natural majority (garlic and pepper) and its matter prevails highly organic in polyethylene cover presentation, obtaining this way an innovative product ace for its ingredients and presentation since is to product clever to serve. The main reason why the research was done lies on the effect of implementation of this microempresa will use meat of organic shrimp, which will be processed to obtain a marine product with added value, where one of our main objectives will be the care of the environment and to offer the consumer a healthy, novel product and mainly guaranteed then it fulfils the norms demanded for elaboration of foods. The study embraces an analysis of financial viability to detail the costs that it implies the creation and development of this microempresa, the revenues that obtain and in that way, with financial approaches and taking like base the market study, the convenience of the project.